Analysis of the Implementation of Results the Development Plan Deliberation on Road Infrastructure Development in Medan Tuntungan District, Medan City - Sanri Kevin Naibaho; Sirojuzilam Sirojuzilam; Agus Purwoko (Sekolah Pascasarjana Universitas Brawijaya, 2019)
This study aims to describe the facts about the level of accommodation of community proposals through data on the proposed realization of the results of the musrenbang in the priority scale of sub-districts in the physical field, in accordance with the mandate of the law, which aims at implementing development planning that is oriented to the interests of the community. (Botoom-up planning). However, the opinion that developed in the community considered that musrenbang was considered merely a formality of the government in carrying out the mandate of the law. Departing from the public opinion, the researcher was interested in raising and researching this problem with the object of musrenbang research in Medan Tuntungan sub-district. This study analyzes the problems related to the implementation with qualitative descriptive methods. From the results of the study, it can be concluded that the concept of regional development planning is appropriate, but the real problem is the implementation of the results of the musrenbang in the Medan Tuntungan sub-district which is less accommodated by the government.